Implementasi Metode Ummi dalam Meningkatkan Kemampuan Membaca Al-Qur’an Santri di Pondok Pesantren Al-Khoirot Malang - Rokim; Muhlis, Nur Khozim; Fathih, Muhammad Amin (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
The Ummi method is a method that teaches the Al-Quran in a tartil manner that is in accordance with the science of tajwid. This method is a new method that was founded in 2011 even though it is relatively new. This method has been widely used in institutions throughout Indonesia. including the al-khoirot Islamic boarding school, the alkhoirot Islamic boarding school is an institution that chooses and uses the ummi method in learning the Koran in order to improve the ability to read the Koran in students. The aim of this research is to describe how the Ummi method is used to improve students' reading of the Quran and what obstacles arise when using this method. The method used in this research uses a descriptive qualitative approach, taking the research location at the Al-Khoirot Islamic Boarding School, Malang. Data collection uses interviews, observation and documentation of teachers and students. The research results show: the use of the Ummi method at the Al-Khoirot Islamic boarding school is considered an effective method in improving the ability to read the Qur'an with the existence of Quality Control which is not only applied to santi, but also to Qur'an teachers. The obstacles that arise when using the Ummi method are: 1) students pay less attention to what the teacher says. 2) there are students who sleep. 3) their ability to understand.